2022
DOI: 10.1186/s40510-022-00450-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of mechano-sensitive non-coding RNAs in bone remodeling of orthodontic tooth movement: recent advances

Abstract: Orthodontic tooth movement relies on bone remodeling and periodontal tissue regeneration in response to the complicated mechanical cues on the compressive and tensive side. In general, mechanical stimulus regulates the expression of mechano-sensitive coding and non-coding genes, which in turn affects how cells are involved in bone remodeling. Growing numbers of non-coding RNAs, particularly mechano-sensitive non-coding RNA, have been verified to be essential for the regulation of osteogenesis and osteoclastoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…ncRNAs are crucial biological factors and are acknowledged as a revolution for disease management in mechanism research, drug development, and the invention of new biomaterials. ncRNAs have a regulatory role during various phases of the bone remodeling process as reported in various studies (Yan et al, 2022).…”
Section: Regulation Of Osteoclastogenesismentioning
confidence: 87%
“…ncRNAs are crucial biological factors and are acknowledged as a revolution for disease management in mechanism research, drug development, and the invention of new biomaterials. ncRNAs have a regulatory role during various phases of the bone remodeling process as reported in various studies (Yan et al, 2022).…”
Section: Regulation Of Osteoclastogenesismentioning
confidence: 87%
“…These lncRNAs promote osteogenic differentiation by various mechanisms, such as acting as sponges for miRNAs or regulating key osteogenic factors. On the other hand, some lncRNAs negatively regulate osteogenic differentiation, including HOTAIR, 105 ODIR1, 106 SNHG1, 107 UCA1, 108 and more. These lncRNAs inhibit osteogenesis by suppressing specific signaling pathways or inhibiting the expression of osteogenic marker genes.…”
Section: Overview Of Epigenetic Modificationsmentioning
confidence: 99%
“…A study found that miR-29 is downregulated in the gingival tissue of individuals with skeletal Class I occlusion and that this downregulation is associated with an increase in the expression of the target genesCOL1A1 and MMP13, which are involved in the regulation of bone remodeling [55]. In addition, miR-31 is downregulated in the gingival tissue of individuals with skeletal Class I occlusion, and this downregulation is associated with an increase in the expression of the target geneTWIST1, which is involved in regulating craniofacial development [56].…”
Section: Rna Alterations In Skeletal Class I Occlusionmentioning
confidence: 99%